Life cycle assessment: Sustainability of biodiesel production from black soldier fly larvae feeding on thermally pre-treated sewage sludge under a tropical country setting. (1st June 2023) - Seng Liew, Chin; Ren Mong, Guo; Wei Lim, Jun; Raksasat, Ratchaprapa; Rawindran, Hemamalini; Hong Leong, Wai; Devendran Manogaran, M.; Ho Chai, Yee; Chia Ho, Yeek; Ur Rahmah, Anisa; Lin, Chuxia; Shiong Khoo, Kuan; et al.
Highlights: BSFL biodiesel shows lesser environmental impacts than other types of biodiesel. BSFL valorization has 100x lesser global warming potential than sludge landfilling. BSFL lipid content is the most sensitive factor that affects the LCA outcomes. Sludge pre-treatment inflicts the most impact on BSFL biodiesel production. Abstract: More energy is needed nowadays due to global population growth. Concurrently, sewage sludge generation has also increased steadily stemming from the inevitable urbanization. As such, black soldier fly larvae (BSFL) can be potentially deployed to solve both issues. This paper investigates the environmental sustainability of biodiesel production derived from sludge-fed BSFL feedstock. A cradle-to-gate life cycle assessment (LCA) was performed through SimaPro software utilizing the ReCiPe 2016 Midpoint (H) and Endpoint (H) methods. The entire LCA covered 3 main stages, including the thermal pre-treatment of sludge, BSFL rearing and processing, and lastly lipid extraction and biodiesel production. LCA showed that the sludge pre-treatment stage had the highest environmental impact, while BSFL rearing and processing had the least due to the suitable geographical climate. Electricity usage during the pre-treatment stage was the main contributing component, followed by chemical usage during biodiesel production. After normalizing, it was observed that land occupation, marine ecotoxicity, freshwater ecotoxicity and freshwater eutrophication were more impactful than the commonly studied global warming potential (GWP). Lipid content and biodiesel conversion efficiency were determined as the sensitive factors which could influence the LCA outcome. In comparison with other types of biodiesel, BSFL biodiesel had a milder impact in terms of climate change, land occupation, terrestrial acidification, marine and freshwater eutrophication. Furthermore, this biological reduction of sludge through BSFL valorization avoided sludge landfilling, which reduced up to 100 times GWP. Therefore, sludge-fed BSFL biodiesel production is an environmentally-sound and highly potential solution that should be investigated comprehensively.